2000
DOI: 10.1038/sj.ijo.0801234
|View full text |Cite
|
Sign up to set email alerts
|

Chronically increased intra-abdominal pressure produces systemic hypertension in dogs

Abstract: OBJECTIVE: Determine if increased intra-abdominal pressure (IAP) alone can cause systemic hypertension in a chronic canine model. DESIGN: Evaluate effects of increase in IAP with progressive in¯ation and de¯ation of an intra-abdominal balloon on systemic blood pressure in experimental and control animals. SUBJECTS: Male dogs weighing 15 ± 25 kg underwent placement of an intra-abdominal balloon which was progressively in¯ated on a weekly basis in the experimental animals (5) over 4 weeks to 25 mmHg above baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…This may stimulate renal sodium retention and may contribute to hypertension. In support of this hypothesis, artificially and chronically increasing intra-abdominal pressure in dogs resulted in hypertension (148). Cardiopulmonary Factors.…”
Section: Other Potential Hemodynamic Factorsmentioning
confidence: 58%
“…This may stimulate renal sodium retention and may contribute to hypertension. In support of this hypothesis, artificially and chronically increasing intra-abdominal pressure in dogs resulted in hypertension (148). Cardiopulmonary Factors.…”
Section: Other Potential Hemodynamic Factorsmentioning
confidence: 58%
“…This was confi rmed in a porcine model where a cinch was placed around the right renal vein after left nephrectomy which was associated with a decreased GFR, increased aldosterone and renin, as well as proteinuria [ 43 ]. In another study, we found that chronically elevated IAP in a canine model led to the progressive development of systemic hypertension which resolved with restoration of a normal IAP [ 44 ]. Others have suggested that the increased ICP with central obesity and increased IAP is responsible for hypertension via the central nervous system [ 42 ].…”
Section: Discussionmentioning
confidence: 65%
“…[41][42][43][44] Furthermore, experimentally induced reductions in splanchnic vascular capacitance elevate blood pressure via an increase in TPR. 45,46 Net transfer of even a small quantity of blood from veins into the arterial system could elicit an increase in vascular resistance through myogenic arterial contraction caused by activation and/or upregulation of voltage-sensitive calcium channels. 47 …”
Section: Discussionmentioning
confidence: 99%